Assessment of the Use of Spinal Anesthesia for laparotomy: A Survey among French-speaking anesthetists - Manika Muteya, Michel; 1Iteke Fefe , Karl Rivain; Sagboze Zalambo , Sandra; Ouattara , Abdoulaye; Mulewa Umba , Déogracias; Matanda Kapend , Serge; Kasamba Ilunga , Eric; Mbuyi Musanzayi , Sébastien; Barhayiga Nsimire , Berthe (International Journal of Scientific Research and Management (IJSRM), 2023)
Introduction. The aim of this survey was to assess the use of spinal anesthesia for abdominal surgery among anesthesia practitioners in sub-Saharan Africa. Methods. A questionnaire was distributed among the participants at the 37th Congress of the Society of Anesthesia-intensive Care Medicine of French-Speaking Africa held in Cotonou, Benin from November 23 to 25, 2022. Participants working in abdominal surgery anesthesia were selected randomly. The most relevant variables for evaluation were the use of spinal anesthesia, type of abdominal surgery, the type of local anesthetic, the additive of anesthetic, the satisfaction of the patients, the acceptance of this anesthesia by the surgeon and the reasons of switching from spinal to general anesthesia. Results. The study included forty-eight anesthesiologists from different nationalities in French-speaking Africa. Most of those practitioners were Anesthetist-Intensive Care Doctors (71%), 44% had between 10 and 15 years of professional experience. Spinal anesthesia is used for laparotomies by 83% of anesthetists. According to the type of surgery, inguinal hernia (85%), hysterectomy (69%) and myomectomy (75%) were found to be the most indications. Participants reported that 79% of the surgeons readily accept performing a laparotomy under spinal anesthesia, and patients are satisfied in 86% of cases. Bupivacaine and Fentanyl are the most local anesthetic used (79%). As adjuvants Morphine and Clonidine were used in 58% and 40% of cases, respectively. The main reasons for switching from spinal anesthesia to general anesthesia (GA) was the failure of spinal anesthesia (48%), followed by long duration of the intervention (19%). Conclusion. The use of spinal anesthesia is reserved mostly by anesthesiologists for lower laparotomies and never for upper laparotomies. There is not enough data to support the evidence that spinal anesthesia can used safely in emergencies situations for supra-mesocolic laparotomies, especially for peritonitis. This call clinical studies which can demonstrate the feasibility, security et safety of laparotomy performed under spinal anesthesia in limited resources settings.